The consumer price index - Federal Office of Statisics; Federal Republic of Nigeria (Lagos : Federal Office of Statistics, 1980)
This report series measured changes in consumer prices of goods and services consumed by urban and rural households in the country.
asm; 10/04/19
Loans
Keywords: Price indexes; Nigeria